Design Of Thermal Climate Test Chamber For Smart Building Investigation - Shiridharan, Ganesan Muthi (UTeM, 2009)
This project of designing and application of a system to control the HVAC system is divided in two parts. First part of the project is about proposal and the second part is about producing the system. This report fully describes about the combination of both part, which contains six chapters starting from introduction, literature review, methodology, results, discussion and conclusion respectively. The main objective of the project is to buy and apply an existing smart system that control the cooling load of HVAC unit based on the heat load of the environment. There will be a testing chamber being built to conduct the test on the smart system. The conceptual design of the platform of testing chamber has been done through sketching by using free hand. After that, the design of the platform of testing chamber was being created by using software such as Solidwork. The process of manufacturing of the platform of testing chamber is done after completing the assembly design in software. This system will be using heat sensor to activate the HVAC system and alter the cooling load from HVAC system depending on the heat load of the environment. The experiment was done successfully. The data was tabulated and graph drawn with discussion based on graph is done. The conclusion is only two of three objective was achieved. The platform was built and experiment was conducted in it. It is found that the air condition unit has only smart system to control the temperature only.